The Drunk, the Insane, and the Criminal Courts: Deciding What to Make of Self-Induced Insanity - Lawrence P. Tiffany (Washington University Law Quarterly, 1991)
There are genuine cases of involuntary intoxication, temporary insanity, and automatism that are actuated by the combined influence of an ingested substance and a preexisting condition of the body or the mind. Many of these cases have been categorized historically as a pathological reaction to alcohol or, what is the same thing, pathological intoxication. We now know that frequently these episodes are phenomena in which an underlying brain abnormality is aggravated by alcohol consumption causing temporary insanity and sometimes violence directed at others nearby. Some courts fail to realize that what contributes significantly to the distinctions between the legal categories of drunkenness and insanity (or automatism), and voluntary and involuntary intoxication is the fault of the actor-the actor's awareness of probable consequences-in bringing about the physical or mental condition. In what amounts to an extension of the same oversight, those courts treat involuntary intoxication, temporary insanity, or automatism resulting from knowing consumption of alcohol as inculpatory fault on the part of the drinker, regardless of whether any reason existed for that person to recognize the possibility of an atypical reaction to the alcohol. Other courts-most of them, fortunately- permit the jury to treat the actor's ensuing mental impairment as a factual basis for a possible defense, unless they additionally find that the actor was culpable in bringing about his or her own mental incapacity.
Keywords: Criminal liability